Phenyl‐γ‐valerolactones, flavan‐3‐ol colonic metabolites, protect brown adipocytes from oxidative stress without affecting their differentiation or function. Issue 9 (12th April 2017) - Mele, Laura; Carobbio, Stefania; Brindani, Nicoletta; Curti, Claudio; Rodriguez‐Cuenca, Sergio; Bidault, Guillaume; Mena, Pedro; Zanotti, Ilaria; Vacca, Michele; Vidal‐Puig, Antonio; Del Rio, Daniele
Abstract : Consumption of products rich in flavan‐3‐ols has been associated with increased energy expenditure. However, phenyl‐γ‐valerolactones (their major colonic metabolites) do not influence brown adipocyte differentiation or function in vitro . Accordingly, they do not modulate the expression of brown adipocytes markers. Moreover, they do not affect mitochondrial content or enhance norepinephrine‐stimulated lipolysis. Nevertheless, they can prevent an increase in reactive oxygen species. Abstract : Scope: Consumption of products rich in flavan‐3‐ols, such as tea and cocoa, has been associated with decreased obesity, partially dependent on their capacity to enhance energy expenditure. Despite these phenolics having been reported to increase the thermogenic program in brown and white adipose tissue, flavan‐3‐ols are vastly metabolised in vivo to phenyl‐γ‐valerolactones. Therefore, we hypothesize that phenyl‐γ‐valerolactones may directly stimulate the differentiation and the activation of brown adipocytes. Methods and results: Immortalized brown pre‐adipocytes were differentiated in presence of (R)‐5‐(3′, 4′‐dihydroxyphenyl)‐γ‐valerolactone (VL1), (R)‐5‐(3´‐hydroxyphenyl)‐γ‐valerolactone‐4′‐ O ‐sulphate (VL2), (R)‐5‐phenyl‐γ‐valerolactone‐3´, 4´‐di‐ O ‐sulphate (VL3), at concentrations of 2 or 10μM, whereas fully differentiated brown adipocyte were treated acutely (6‐24h). None of the treatments regulated the expression levels of the uncouple protein 1, nor of the main transcription factors involved in brown adipogenesis. Similarly, mitochondrial content was unchanged after treatments. Moreover these compounds did not display peroxisome proliferator‐activated receptor γ‐agonist activity, as evaluated by luciferase assay, and did not enhance norepinephrine‐stimulated lipolysis in mature adipocytes. However, both VL1 and VL2 prevented oxidative stress caused by H2 O2 . Conclusion: Phenyl‐γ‐valerolactones and their sulphated forms do not influence brown adipocyte development or function at physiological or supraphysiological doses in vitro, but they are active protecting brown adipocytes from increased reactive oxygen species production.